Preliminary Physico-Chemical and Phytochemical Study of Seeds of Balanites Aegyptiaca - Moutaly, Mohamed; N’diaye, Abdoulaye Demba (ASEAN Journal for Science and Engineering in Materials, 2022)
The Balanites aegyptiaca is an important tree found in some African countries. This study aimed to assess the seeds of the Balanites aegyptiaca physicochemically and phytochemically. pH, Moisture, ash, protein, and lipid contents of Balanites aegyptiaca seeds are 5.8, 2.10%, 5.6%, 17.5%, and 10.7%, respectively. The mineral elements analysis showed that the Balanites aegyptiaca is rich in calcium (247.4 mg/100 g), potassium (140 mg/100 g), sodium (30 mg/100 g), magnesium (24.6 mg/100 g), iron (8.50 mg/100 g) and zinc (5.50 mg/100 g). The result suggests that the seeds of Balanites aegyptiaca fruits could contribute greatly towards meeting the human nutritional requirement for normal growth. The presence of several phytochemical compounds showed high therapeutic potential of Balanites aegyptiaca and it can take for medicinal purposes after determining the seeds pharmacologically.